Combining ability and heterosis studies for yield, grain iron and zinc content in pearl millet (Pennisetum glaucum) - SHAILESH KUMAR JAIN; SHARWAN KUMAR SHARMA; D K GUPTA; VIKAS KHANDELWAL; ROHIT KUMAR SHARMA; ANURADHA; VAIBHAV SHARMA; B L DHAKA; S K GUPTA (The Indian Journal of Agricultural Sciences)
Pearl millet (Pennisetum glaucum L.) is a vital food crop in semi-arid regions of Asia and Africa. The present study was carried out during summer and rainy (kharif) season of 2023 at Rajasthan Agricultural Research Institute (Sri Karan Narendra Agriculture University, Jobner, Jaipur, Rajasthan), Durgapura, Jaipur, Rajasthan to enhance iron (Fe) and zinc (Zn) content in pearl millet. The experimental material included 127 entries, comprising 105 crosses, 15 male-sterile lines, and 7 testers. The experiment was laid out in a randomized block design (RBD) with three replications across the two environments. The study revealed significant genetic diversity among parents and hybrids, particularly for Fe and Zn. The analysis of general combining ability (GCA) revealed significant differences among lines and testers across environments. Key general combiners for grain yield were P4 and P11, while P5, P11, P12, and P13 contributed significantly to fodder yield. For Fe and Zn enhancement, P1 and P3 emerged as effective combiners. Among 105 hybrids, 30 exhibited significantly positive specific combining ability (SCA) for grain yield, while four and five hybrids showed positive SCA for Fe and Zn, respectively. Notably, 89 hybrids displayed positive heterosis for grain yield. Fe content ranged from 20.83–83.50 ppm, with two hybrids showing significant positive heterosis, whereas Zn content varied from 20.00–57.17 ppm, with five hybrids performing well. Limited positive mid-parent and better-parent heterosis for Fe and Zn suggested heterosis has restricted potential for micronutrient improvement. The study underscores the need to incorporate Fe and Zn into parental lines for effective hybrid development. Hybrids P1 × P19 and P14 × P18 were promising for micronutrient enhancement, supporting strategic breeding for yield, fodder, and nutritional quality.